Field lab Sme competitiveness - edudigital´s internationalization strategy - Gomes, Francisco Da Costa Neto Tavares (2021)
EDU digital is currently struggling with its internationalization process, generating profits and being established in the African market. The goal of this study is to analyze the global readiness of the firm and to evaluate new markets. The assessment was made through a Country Clustering and Ranking, followed by an in-depth analysis of the top five countries. A strategic plan was developed in three stages: definition of the international entry strategy, elaboration of a marketing strategic plan and computation of a financial forecast. The results prove the firm’s preparedness to go global and that Sweden is the optimal target.